Data base of Power and electromyographic activity in college volleyball players - Aedo-Muñoz, Esteban (2020)
Aedo-Muñoz, E., Tamayo Contreras, V., Rojas Reyes, C., Hernández Wimmer, C., Brito, C., Miarka, B., Arghoty Bucheli, R., Dal Bello, F & Herrera Valenzuela, T. (2020). Power and electromyographic activity in college volleyball players. Pensar en Movimiento: Revista de Ciencias del Ejercicio y la Salud, 18(1), 1-14. The purpose of this study was to determine the relative power of lower limbs and the surface electromyographic activity (EMG) of the gluteus maximus (GM), vastus medialis (VM), vastus lateralis (VL), and lateral gastrocnemius (GASLAT) during a countermovement jump (CMJ) and an Abalakov jump (ABK). Twenty-four college volleyball players were divided into two equal groups assigned by division: Group 1 (G1), comprised of volleyball players from the 1st university division, and Group 2 (G2), comprised of volleyball players from the 2nd university division. Both groups took two simultaneous EMG and power assessments. For the power assessment, a 2D recording system was used to track the greater trochanter with a 250fps camera. The video was analyzed with the Tracker 4.96 software to obtain absolute power values. The EMG activity was measured using a Delsys Trigno® electromyograph in the GM, VM, VL, and GASLAT muscles. Significant differences were found in %PeakRMS of VL (G1=65.210.2; G2=54.0±11.7 %PeakRMS; p<0.05) for CMJ, as well as in VL (G1=69.6±17.3; G2=55.1±12.3 %PeakRMS; p<0.05) for ABK and GASLAT (G1=61.4±13.4; G2=50.6±7.2 %PeakRMS; p<0.05).  Regarding relative power, no significant differences were present between CMJ (p> 0.05) and ABK (p>0.05).